Perlindungan Konsumen Terhadap Peredaran Produk Makanan Impor Berlabel Bahasa Asing (LEGAL DIALOGICA, 2025)
This study aims to determine and analyze the implementation of consumer protection against the circulation of imported food products labeled in foreign languages ​​in Makassar City and legal efforts to protect consumers against the circulation of imported food products labeled in foreign languages. This study uses an empirical approach method. This study focuses on the reality or legal reality in the community environment (law in action). Facts in the field related to implementing consumer protection against the circulation of imported food products labeled in foreign languages ​​in Makassar City by the Food and Drug Supervisory Agency (BBPOM). The results of the study indicate that the implementation of consumer protection against the circulation of imported food products labeled in foreign languages ​​in Makassar City under the auspices of the Makassar City Food and Drug Supervisory Agency has not been running optimally, as indicated by the existence of imported products labeled in foreign languages ​​that are still circulating in shops in Makassar City. Consumers who find violations or feel disadvantaged by the circulation of imported food products labeled in foreign languages ​​by business actors can take legal action by complaining to the Consumer Complaints Service (LPK) of the Food and Drug Supervisory Agency without any fees. The recommendation of this study is the importance for business actors and consumers to know their respective rights and obligations. Then, the importance of being a smart consumer is the first form of self-defense by paying attention to every food product that will be consumed, because consumers are the ones who will ultimately feel the impact of the products they consume.Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis implementasi perlindungan konsumen terhadap peredaran produk makanan impor berlabel bahasa asing di Kota Makassar dan upaya hukum perlindungan konsumen terhadap peredaran produk makanan impor berlabel bahasa asing. Penelitian ini menggunakan metode pendekatan empiris. Penelitian ini berfokus pada realitas atau kenyataan hukum di dalam lingkungan masyarakat (law in action). Fakta yang ada di lapangan yang terkait dengan fenomena implementasi perlindungan konsumen terhadap peredaran produk makanan impor berlabel bahasa asing di Kota Makassar oleh Balai Besar Pengawas Obat dan Makanan (BBPOM). Hasil Penelitian menunjukkan bahwa Implementasi perlindungan konsumen terhadap peredaran produk makanan impor berlabel bahasa asing di Kota Makassar dibawah naungan Balai Besar Pengawasan Obat dan Makanan Kota Makassar belum berjalan secara optimal, ditandai dengan masih adanya produk impor berlabel bahasa asing yang masih beredar di toko-toko yang ada di Kota Makassar. Konsumen yang menemukan pelanggaran ataupun merasa dirugikan atas peredaran produk makanan impor berlabel bahasa asing oleh pelaku usaha, dapat melakukan upaya hukum dengan pengaduan ke Layanan Pengaduan Konsumen (LPK) Balai Besar Pengawas Obat dan Makanan tanpa adanya pungutan biaya. Rekomendasi penelitian ini adalah pentingnya bagi pelaku usaha dan konsumen mengetahui hak dan kewajibannya masing-masing. Kemudian, pentingnya menjadi konsumen  yang cerdas menjadi bentuk pertahanan diri pertama dengan memperhatikan setiap produk makanan yang akan dikonsumsi, karena konsumen lah yang pada akhirnya akan merasakan dampak dari produk yang dikonsumsi.